Green Synthesis of Silver Nanoparticles with Bioreductant from Lime Juice Powder (Citrus aurantifolia): Effect of Concentration and pH - Mulyana, Septian Dwi; Sari, Retno; Rijal, Agus Syamsur (Indonesian Journal of Chemistry, 2024)
Significant development in antibacterial agents derived from metal nanoparticles is currently underway. One commonly employed type is silver nanoparticles (AgNPs), which display potential antibacterial activity at lower concentrations compared to other metals. Due to their high surface-to-volume ratio and small size, AgNPs can readily penetrate bacterial cell walls. Green synthesis methods of AgNPs, such as utilizing plants as reducing agents, offer substantial advantages over other synthesis techniques. Lime (Citrus aurantifolia), containing compounds like flavonoids and saponins, can serve as a natural reducing agent, converting Ag+ ions to Ag0. This study aims to evaluate the effects of AgNO3 concentration, lime juice powder concentration, and pH on the formation and characteristics of AgNPs, as well as their activity against the bacteria Propionibacterium acnes, Staphylococcus aureus, and Escherichia coli. Results indicate that at an AgNO3 concentration of 1 mM, lime juice extract at 1% with a pH of 9 produces optimal AgNP formation, with an absorbance of 4.631 and particle size of 68.4 nm. AgNPs exhibit higher antibacterial activity than AgNO3. AgNPs synthesized with lime juice powder can increase their activity and have the advantages of being safe and environmentally friendly since they use plant material as a reducing agent.